Model Shrinking Core Pada Isolasi Kitosan Dari Limbah Ebi - Rani Handayani; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitosan is derived from chitin compound used in the biomedical field. Chitosan can be synthesized from ebi waste using chemical methods through the deproteination, demineralization and the deacetylation processes. The aims of this study are to determine the effect of NaOH concentration on the degree of deacetylation chitosan synthesis and to determine the model that can describe the kinetics reaction via Shrinking Core Model (SCM) approach. The procedure of research was started by ebi waste size reduction. Ebi powder was reacted with NaOH 3.5% (deproteination), ratio 1:10 (w/v) for 2 hours stirring by 150 rpm. The deproteination product was reacted with HCl 1 N (demineralization), ratio 1:15 (w/v) for 1 hour stirring by 150 rpm. Then the product was reacted using NaOH 40%, 50%, and 60% (deacetylation), ratio 1:20 (w/v) at a temperature of 120oC with stirring by 150 rpm for 2 hours. Samples were taken every 10 minutes rise as much as 10 mL, washed until pH neutral and it dried. Deacetylation degree of chitosan was analyzed using acid-base titration method. The results showed that the higher the concentration, the higher the degree of deacetylation of the chitosan will be namely 72.63% to 79.32% at a temperature of 120oC. The best reaction kinetics model to describe the occur in the synthesize of chitosan was a model 2, that was a layer (chitosan) to control with the equation as:Model 2 is the best kinetic’s model with shrinking reacted core model on synthesize of citosan and ebi waste.Keywords: deacetylation, reaction kinetics, chitosan, waste ebi, shrinkingcore model.